The Effect of Task-Based Language Learning and Learning Styles on the Students’ Reading Ability - Mubarok, Husni; Sofiana, Nina (Universitas Negeri Semarang, 2017)
This study was aimed at examining the effect of task-based language learning (TBLL) and learning styles on students‘ reading ability. The research design of this study was experimental research in the form of factorial design. The population of this study was the eighth grade students of Islamic Junior High School in Jepara Municipality under The Ministry of National Education. The sampling used was simple random sampling which reached 68 respondents. Variables in this study were 1) independent variables (the use of task-based language learning to experimental group and conventional teaching strategy to control group), 2) moderator variable (students‘ learning styles; visual and auditory), and 3) dependent variable (students‘ reading ability). To test the hypothesis, this study used multifactor analysis of variance (MANOVA). The result revealed that started in the similar reading ability, regardless of the students‘ learning styles, students treated under TBLL had better achievement than those treated under conventional teaching strategy (81.32 > 72.21). Therefore, TBLL was more effective than conventional teaching strategy (F>7.04 and p: .01). Then, students‘ learning styles differ significantly from one another in their effect on students‘ reading ability. Regardless of the teaching strategies, visual students performed better than auditory students (79.12 > 74.41). Finally, the data revealed no interaction between teaching strategies and students‘ learning styles; the value of F, 4.284, was not significant because it was smaller than the values shown in the table. It indicated that they were independent of each other; the effect of teaching strategies did not depend on the students‘ learning styles.